In the valley of the Kauravas: a divine kingdom in the Western Himalaya - Sax, William Sturman (Oxford University Press, 2024)
In Western Himalaya, local gods are seen to rule as kings, communicating with their subjects through their human oracles. They remain central in modern society, and 'In the Valley of the Kauravas' explores how the power of the local gods and oracles remains by examining the myths, legends, rituals, and folklore of the region.
Also issued in print: 2024. - Includes bibliographical references and index. - Description based on online resource and publisher information; title from PDF title page (viewed on October 23, 2023)
Keywords: Mahābhārata -- Influence; Ethnologie; Sakralkönigtum; Gottkönig; Himachal Pradesh